Bacterioplankton Richness and Composition in a Seasonal Urban River - Xiao, Zufei; Li, Gang; Zhao, Yi; Xiao, Keqing; Chen, Qinglin; Bao, Peng; Tang, Jianfeng; Ruan, Tian; Zama, Eric Fru; Xu, Yaoyang (Frontiers in Environmental Science, 2021)
Urbanization and seasonality strongly influence the bacterial composition of the soil. However, aquatic environments such as rivers are understudied owing to their high dynamics and therefore rules relating to more static habitats such as lentic or terrestrial environments may be limited. Here, we compared the spatiotemporal patterns of bacterioplankton communities in the Zhangxi river along a gradient of urbanization using 16S ribosomal DNA identification. The alpha and beta diversity of bacterioplankton showed no significant response to watershed urbanization. A significant difference in predicted functional profiles of the bacterioplankton community was also revealed between the wet and dry seasons. The bacterioplankton community assembly was driven by both deterministic and stochastic processes. Stochasticity was one of the most vital processes affecting the bacterioplankton communities in both wet and dry seasons, explaining over 50% variation in the community by the null model analysis. Bacterioplankton co-occurrence patterns in the river changed with the seasons. More notably, the composition of bacterioplankton communities was inconsistent with alternations of the spatial distance offering meaningful implications for interactions between zero-radius operational taxonomic units and the dynamics of the bacterioplankton communities in surface water. In summary, we found clear patterns of seasonal variations in the bacterioplankton community structures.